Discourse Markers of Humor Analysis in Trevor Noah’s Stand-Up Comedy - Rofiq, Zainur; Priyono, Eko Suci (Lingual Journal of Language and Culture; Vol 11 No 1 (2021): Lingual: Journal of Language and Culture, 2021)
Discourse markers have been widely studied in various discourses such as political discourse, legal, media discourse, and even daily conversation. However, there is still a lack of discourse markers research in humor studies. This study was projected to identify the linguistic aspects of humor genre utterances in stand-up comedy performed by Trevor Noah as one of the most influential stand-up comedians. In addition, those linguistic aspect is discourse markers. The data were taken from Trevor Noah’s Video entitle "Prince Harry & Meghan Markle's Royal Wedding" Live at the O2 London. Afterward, the data were analyzed by using the theoretical framework of discourse marker and its pragmatic functions introduced by Brinton (1996). This study reveals that there are several types of discourse markers used in stand-up comedy, such as “ah”, “and”, “like”, “oh”, “alright”, “then”, “huh”, “well”, “yes/no” , and “I know/knew”. In addition, all of those discourse markers have different functions, and sometimes one discourse marker serves more than one pragmatic functions.